INTERACTIVE MULTIMEDIA USE OF GAMES MODEL ON IPS SCHOOL STUDY LIST - Febby Fajar Nugraha (PrimaryEdu : Journal of Primary Education, 2017)
The development of information and communication technologies have a major impact in many areas of life, one of which is education. Learning use the media, is a strategy favored by students, particularly those related to technology. Because no denying that the interest of students to current technologies is huge. It can be seen from the children of school age, who loss of learning time because they are pre occupied with the world of technology, such as playing games, mobile phones and computers. Indonesian Internet Service Provider Association (APJII) conducted a survey of online game players active in Indonesia, the result is there are about 6 million online game players. This proves that Indonesian children have an interest in the game.  The change of curriculum in Indonesia from 2006 curriculum (Curriculum Education Unit) into a curriculum 2013, providing a wide range of implications for the learning process, one of which is the subject of Information and Communication Technology (ICT). In curriculum 2013, ICT subjects be erased, it’s means not stand alone but rather merged or combined with other subjects. In elementary school curriculum needs  subjects that are combined with computer lessons (Guha &Leonard, 2002). Therefore, teachers must be able to create methods that can capitalize on technology such as computer media in the learning process.Keywords: Computer, Interactive multimedia games model, Social Studies, Elementary school , and Understanding of concepts.